A contemporary tool for assessing instrumental activities of daily living: Validation of a caregiver-reported scale for non-institutionalized older adults - Zainab Barakat; Hala Sacre; Sarah Khatib; Aline Hajj; Carmela BouMalham; Chadia Haddad; Rony M. Zeenny; Marwan Akel; Linda Abou Abbas; Marc Barakat; Samar Rachidi; Pascale Salameh (PLoS ONE, 2025)
Background Instrumental activities of daily living (IADL) refer to activities necessary for independent living, emphasizing community-related tasks. The literature has limited measurement tools that address autonomous living in contemporary communities. Consequently, our study aimed to develop, cross-culturally adapt, and evaluate the psychometric properties of a recently updated IADL scale called the Autonomy in Daily Functioning-Contemporary Scale (ADF-CS). Additionally, it sought to examine the level of agreement between informant reports and self-reports on the ADF-CS. Method Following translation and cross-cultural adaptation, a first cross-sectional study was carried out among 544 family caregivers of community-dwelling older adults to assess the psychometric properties of the ADF-CS. The internal consistency of the scale was evaluated via Cronbach’s alpha. Content and convergent validity, factorial analysis—including confirmatory factor analysis (CFA) and exploratory factor analysis (EFA)—and known group validity were also assessed. A second cross-sectional study involving 44 paired caregivers and care recipients was conducted to examine the level of agreement in responses to the ADF-CS scale between caregivers and older adults. Response agreement was evaluated through intraclass and Cohen’s kappa correlation coefficients. Results The internal consistency of the ADF-CS and its factors was high (Cronbach’s alpha between 0.83 and 0.90). The robust positive correlation between the total ADF-CS score and the ADL score supported the convergent validity of the ADF-CS Arabic version. Moreover, the statistically significant variations in ADF-CS mean scores among various age groups and some chronic disease groups supported the scale’s known group validity. The EFA of the ADF-CS yielded a two-factor solution with an eigenvalue exceeding 1, explaining 63.13% of the variance. The CFA demonstrated that all the items in each component fit well with their intended constructs. Additionally, the intraclass and kappa correlation coefficient results were excellent, indicating robust agreement in the responses of caregivers and their respective older adults. Conclusion The Arabic version of the ADF-CS is a reliable and valid informant-reported measure for assessing IADL in older adults living in a contemporary community.